Metacognitive awareness of listening strategies in L2 English and L3 Italian - Öztekin, Elifcan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Transfer of language skills across languages has been an essential question in the field of bilingualism. Theoretical approaches to this issue proposed assumptions on metacognitive awareness defined as learners’ own introspective consciousness on their learning processes. Second language (L2) research on language skills has investigated transfer issue especially in reading skills; however, there is limited research on the transfer of language skills in third language (L3) learning and listening skills and strategies. To address this gap, the current study examined the role of metacognitive awareness in listening strategies in an L2 English L3 Italian context with university students in Turkey. The study explored learners’ metacognitive awareness of listening strategies in their more proficient L2 compared to their less proficient L3, and whether L2 and L3 metacognitive level correlated with L3 listening comprehension. To this end, a questionnaire of metacognitive awareness of listening strategies in L2 and L3, and a listening comprehension test in L3 were implemented. Results indicated higher levels of metacognitive awareness in certain strategies depending on the language, pointing to the role of proficiency in the use of listening strategies. In addition, metacognitive awareness of listening strategies in L2 and L3 were significantly correlated, suggesting possible transfer of skills across languages. Finally, the results yielded a direct relationship between L3 proficiency and L3 listening comprehension while L2 proficiency was not related to L3 listening comprehension.
Keywords: English language -- Study and teaching.; Second language acquisition -- Study and teaching.; Italian language -- Study and teaching.